Grain yield and physiological parameters of gas exchange in common bean as a function of copper fertilization (Research, Society and Development, 2021)
Conducting a field study to investigate the effects of foliar and soil fertilization with copper on the nutritional and physiological parameters and grain yield of common bean. The experimental design was a randomized block, in a 2 x 5 factorial scheme. The first factor was the site of application of copper fertilization. The second factor was copper doses: 0, 1, 2, 3, and 4 kg ha-1 (6 replicates). The following were evaluated: leaf nitrogen and copper contents, relative chlorophyll index (RCI), gas exchange, photochemical efficiency of photosystem II, and grain yield. The data were subjected to analysis of variance and F test (p-value < 0.05), using the Scott & Knott for qualitative data and polynomial regression for quantitative data. Leaf Cu content was higher with soil application (4% and 28%), both at 24 and 45 DAE, respectively. Net photosynthesis reached a maximum index of 18.77 µmol m-2 s-1 with foliar Cu fertilization at the dose of 4 kg ha-1. The application of 2.0 kg ha-1 Cu was the one that led to the highest grain yields; however, soil application stood out with a yield about 12% higher of the foliar. Soil fertilization proved to be more efficient in terms of Cu absorption and RCI rates, improving grain yield (12%) in relation to foliar, especially at the dose of 2 kg ha-1. The dose of 2 kg Cu ha-1 provided the best differential profit, reaching US$ 581.96 ha-1 and US$ 503.01 ha-1 for soil and foliar application, respectively.